Novel Fluorinated Spermine and Small Molecule PEI to Deliver Anti-PD-L1 and Anti-VEGF siRNA for Highly Efficient Tumor Therapy - Yihui Zhang; Zihan Yuan; Yi Jin; Wenkai Zhang; Wei-En Yuan (MDPI AG, 2021)
Small interfering RNA (siRNA) can specifically silence disease gene expression. This project investigated the overexpression of programmed death receptor ligand 1 (PD-L1) and vascular endothelial growth factor (VEGF) on the surface of tumor cells. However, the main obstacle to the development of gene therapy drugs is the lack of an efficient delivery vector, which should be able to overcome multiple delivery barriers and protect siRNA to enter the target cells. Therefore, a novel fluorine-modified endogenous molecular carrier TFSPEI was constructed by linking fluorinated groups with hydrophobic and hydrophilic characteristics on the surface of PEI and spermine. The results showed that lower toxicity, higher endocytosis, and silencing efficiency were achieved. We found that the inhibition of VEGF targets can indirectly activate the immune response to promote the tumor-killing and invasion effects of T cells. The combined delivery of anti-VEGF siRNA and anti-PD-L1 siRNA could inhibit the expression of corresponding proteins, restore the anti-tumor function of T cells and inhibit the growth of neovascularization, and obtained significant anti-tumor effects. Therefore, this safe and efficient fluorinated spermine and small molecule PEI-based anti-PD-L1 and anti-VEGF siRNA delivery system is expected to provide a new strategy for gene therapy of tumors.